Investigate innovative teaching strategies that improve elementary school students' speaking skills in the digital age - Muchamad Fauyan; Anwar Efendy; Sugeng Bayu Wahyono (Journal of Integrated Elementary Education, 2026)
This study aims to identify effective strategies for improving the speaking skills of fifth-grade elementary students through innovative pedagogical approaches, technology integration, and socio-emotional support. This research employed a mixed-methods approach using a convergent parallel design. Participants consisted of ten fifth-grade teachers from ten elementary schools or madrasah ibtidaiyah in Pekalongan City selected purposively based on their teaching experience, and twenty students randomly selected from the same classes. Qualitative data were collected through structured interviews and classroom observations, while quantitative data were obtained using four-point Likert-scale questionnaires measuring instructional strategies, student engagement, speaking confidence, and the use of educational technology. The findings show that teachers employ diverse student-centered strategies—such as contextual, cooperative, and collaborative learning, storytelling, problem-based learning, project-based learning, and interactive discussions supported by digital media—to create meaningful speaking opportunities; quantitatively, more than 90% of teachers consistently implemented guided speaking practices that increased participation and 80% of students showed enthusiasm in collaborative speaking activities, although technology integration remained moderate among about 30% of teachers and 40–80% of students still demonstrated limited confidence in individual or spontaneous speaking tasks. These findings highlight the importance of integrating innovative instructional strategies, digital learning technologies, and socio-emotional support in speaking instruction.